PENGARUH KESELAMATAN KESEHATAN KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAAN KARYAWAN PADA PT THAMRIN BROTHERS PALEMBANG. - Sindang Sari (STIE DWI SAKTI BATURAJA, 2019)
The research objective was to determine the effect of occupational health and work environment on jobsatisfaction both jointly and partially at PT Thamrin Brothers Palembang. The type of research used isassociative research. The research aimed to find out the relationship between variables, namely the variablesof occupational health and work environment towards employee satisfaction of the company PT ThamrinBrothers Palembang. The design used in this study is correlational design. The population of this study wereall 112 employees of PT Thamrin Brothers Palembang. Sampling technique is a sampling technique in thisstudy that is by probability sampling technique with the sampling technique using simple random sampling.The first sample was tested using the Instrument Test (questionnaire) in the form of validity test andreliability test. The analysis model used in this study is multiple linear regression analysis.Through multiplelinear regression calculations. The constant coefficient (α) is 1.599, the coefficient for occupational healthsafety variable (X1) is 0.325, and the work environment variable (X2) is 0.887. The value of F count (19,817)>Ftable (3,10), with the level of sig.F 0,000 <0,05 (significant. This means there is an influence of occupationalhealth safety and work environment on employee satisfaction at PT. Thamrin Brothers Palembang.Tcount(2.333)> t table (1.988), with a level of sig.t 0.006 <0.05 (significant). This means that there is the influence ofoccupational health safety on employee satisfaction at PT. Thamrin Brothers Palembang. Tcount (5,115)> ttable (1,988), with the level of sig.t 0,000 <0,05 (significant). This means that there is the influence of thework environment on employee satisfaction at PT. Thamrin Brothers Palembang. the value of Adjusted RSquare (coefficient of determination) is 0.819, meaning that the variables of occupational health and workenvironment are able to contribute to employee satisfaction by 81.9%. While the remaining 18.1% isexplained by other variables.